(untitled) (Revista Brasileira Multidisciplinar, 2026)
The production of content for social media in the field of health involves evidence-based strategies to communicate science in an accessible manner. This article aims to report the experiences of professionals who lead and participate in research groups, focusing on the promotion of scientific output, events, and collective discussion spaces through social media, thereby fostering a closer connection with real-world contexts. This is a systematized experience report, with a qualitative approach. Based on the experience of the authors who are part of the professional categories of Nursing, Medicine and Nutrition, between the years 2023 and 2024, regarding the production for social media of two research groups, linked to the State University of Ceará. The production for social media of the research groups generates efficient tactical actions for expanding access to scientific information, expanding networks, and social participation. The report suggests that the media produced tend to reach the target audience due to the reliability of the content and accessible language.